Comparison of the effects of α-Tocopherol and γ-Tocotrienol against oxidative stress in two different neuronal cultures - Then, Sue-Mian; Wan Zurinah Wan Ngah,; Gapor Mat Top,; Musalmah Mazlan, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Tocopherols and tocotrienols have been shown in previous studies to protect neurons from oxidative injuries, especially from hydrogen peroxide (H2O2) and buthionine sulfoximine (BSO) induced oxidative stress. In this study, we compared two vitamin E isomers, γ-tocotrienol (GTT) and α-tocopherol (ATF) in their neuroprotective effects against H2O2-induced apoptosis in primary rat cortical neurons and human neuroblastoma cell line SH-SY5Y. Cytotoxicity screening of H2O2, GTT and ATF was done to determine the IC50 levels. To screen for neuroprotective effects, cortical neurons and SH-SY5Y cell cultures were pre-incubated with GTT or ATF, respectively at different concentrations for 1 hour before concurrent treatment of H2O2 at IC50. Results of these treatments were compared to cells treated with H2O2 only and control cells. Cytotoxicology screening showed that IC50 of H2O2 for cortical neuron is at 50 μM while SH-SY5Y have higher IC50 of 100 μM. GTT is cytotoxic to cortical neurons at ≥50 μM and SH-SY5Y at ≥100 μM while ATF did not show any toxicity within the range of concentration tested (1-750 μM). Results from neuroprotection screening showed that GTT and ATF were able to protect both cortical neurons and SH-SY5Y from H2O2-induced oxidative stress at concetration of ≤10 μM. Cellular uptake of GTT is higher in both cortical neurons and SH-SY5Y as compared to ATF when both cortical neuron and SH-SY5Y were incubated with 10 μM GTT or ATF, respectively for 24 hour. Although primary rat cortical neurons and human neuroblastoma SH-SY5Y were different culture system, the effects of GTT and ATF are similar in both H2O2 –induced culture which strongly suggest that both GTT and ATF act as free radical scavenger to exert their neuroprotective effects.